How effective is circuit training on physical fitness? A high-intensity study in the sport of futsal - Suniga, John Paul C.; Custodio, Joselito M.; Roldan, Patrick John B.; Shlool, Hatem A.; Abumoh'D, Mohammad Fayiz (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. Physical fitness is a crucial component that supports optimal performance in sports, including futsal, which demands a combination of endurance, strength, agility and speed. This study aims to analyze the effectiveness of high-intensity circuit training on improving the physical fitness of futsal players.Material and Methods. The research design used a one group pretest-posttest design method, with participants as many as 8 futsal athletes selected using purposive sampling technique. The study was conducted under partly cloudy weather conditions with real-time temperature of 25.3°C, humidity of 94%, and wind speed of 19.4 km/h. This exercise uses 14 fitness equipment, namely triceps, leg press, front pull down, calf raise, butterfly, leg extension, bench press, sit-up, back-up, standing rowing, squat, back pull down, bicep, and leg curl. Exercises were performed in 3 sets per session with maximum repetitions (1 RM) and rest between sets for 4-5 minutes. The program was implemented for 12 sessions, with full intensity 3 times a week. The instrument was carried out using the Yo-Yo Intermittent Recovery Test Level 1. Data analysis was assisted using the SPSS 26 applicationResults. The results showed a significant increase in physical fitness after the treatment was given. The mean pretest and posttest values were statistically different (t = -4.190; p 0.05), with an average improvement of -1.36250. High-intensity circuit training proved to be effective in improving the physical fitness of futsal players, which includes an increase in aerobic capacity and physical strength.Conclusion. This study provides scientific evidence that high-intensity circuit training is an efficient method to improve the physical performance of futsal players. These findings can serve as a reference for coaches in designing relevant and measurable futsal sport needs-based training programs.